2002
DOI: 10.1034/j.1600-0420.2002.800103.x
|View full text |Cite
|
Sign up to set email alerts
|

Central corneal thickness, radius of the corneal curvature and intraocular pressure in normal subjects using non‐contact techniques: Reykjavik Eye Study

Abstract: ABSTRACT.Purpose: To establish a population profile of central corneal thickness (CCT), radius of the corneal curvature (CC) and intraocular pressure (IOP) and the relationships between them using non-contact techniques. Methods: We used a population-based random sample of 415 male and 510 female Caucasians aged 50 years and older. CCT and the radius of CC were measured with Scheimpflug anterior segment photography. IOP was measured with air-puff tonometry. Results: The mean IOP of right eyes was 15.1 mmHg (SD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

27
112
6
3

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 173 publications
(148 citation statements)
references
References 25 publications
27
112
6
3
Order By: Relevance
“…21 Our study found that CCT was positively correlated with IOP in elderly white subjects without visual field defect. A similar relationship has been found in various populations, [21][22][23][24] although it was not present in the black participants of the Barbados Eye Study. 25 IOP measured by Goldmann applanation tonometry should ideally be adjusted for CCT, although a simple nomogram is unlikely to be accurate in all cases due to the influence of other factors such as corneal rigidity.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…21 Our study found that CCT was positively correlated with IOP in elderly white subjects without visual field defect. A similar relationship has been found in various populations, [21][22][23][24] although it was not present in the black participants of the Barbados Eye Study. 25 IOP measured by Goldmann applanation tonometry should ideally be adjusted for CCT, although a simple nomogram is unlikely to be accurate in all cases due to the influence of other factors such as corneal rigidity.…”
Section: Discussionsupporting
confidence: 86%
“…8,10,19,20 Two studies which also only recruited older participants, failed to detect a significant relationship. [21][22][23][24] The changes in structural corneal biomechanics with subject age adds further complexity to the relationship between CCT and Goldmann IOP. 26 The diabetic patients in our study had significantly greater CCTs than the non-diabetic patients, although only by a mean of 9 mm.…”
Section: Discussionmentioning
confidence: 99%
“…We did not consider the corneal curvature because the effect of it on applanation tonometer readings remains uncertain. Using 925 randomly sampled right eyes, Eysteinsson et al 15 could not establish any relationship between the radius of corneal curvature and the NCT measurements. Paranhos et al 23 also found no significant influence of corneal curvature on IOP readings obtained with the GAT and NCT in 404 eyes with keratometric readings between 8.6 and 6.39 mm.…”
Section: Discussionmentioning
confidence: 97%
“…In a population study on subjects aged 50 years or older, Eysteinsson et al 15 found that every 10 mm increase in CCT is associated with a rise of 0.22-0.28 mmHg in NCT (Nidek NT 2000) readings. However, their study did not take into account individual variation in true intraocular hydrostatic pressure while estimating the influence of CCT on IOP readings.…”
Section: Discussionmentioning
confidence: 99%
“…2,3 In vivo, it is measured either by ultrasonography or by partial coherence interferometry. The AL of the eye at birth is approximately 17 mm and reaches approximately 24 mm in adulthood.…”
Section: Introductionmentioning
confidence: 99%